Targeting PARP-1 with metronomic therapy modulates MDSC suppressive function and enhances anti-PD-1 immunotherapy in colon cancer. Issue 1 (25th January 2021) - Ghonim, Mohamed A; Ibba, Salome V; Tarhuni, Abdelmetalab F; Errami, Youssef; Luu, Hanh H; Dean, Matthew J; El-Bahrawy, Ali H; Wyczechowska, Dorota; Benslimane, Ilyes A; Del Valle, Luis; Al-Khami, Amir A; Ochoa, Augusto C; et al.
Abstract : Background: Poly(ADP-ribose) polymerase (PARP) inhibitors (eg, olaparib) are effective against BRCA-mutated cancers at/near maximum tolerated doses by trapping PARP-1 on damaged chromatin, benefitting only small patient proportions. The benefits of targeting non-DNA repair aspects of PARP with metronomic doses remain unexplored. Methods: Colon epithelial cells or mouse or human bone marrow (BM)-derived-myeloid-derived suppressor cells (MDSCs) were stimulated to assess the effect of partial PARP-1 inhibition on inflammatory gene expression or immune suppression. Mice treated with azoxymethane/four dextran-sulfate-sodium cycles or APC Min/+ mice bred into PARP-1 +/− or treated with olaparib were used to examine the role of PARP-1 in colitis-induced or spontaneous colon cancer, respectively. Syngeneic MC-38 cell-based (microsatellite instability, MSI high ) or CT-26 cell-based (microsatellite stable, MSS) tumor models were used to assess the effects of PARP inhibition on host responses and synergy with anti-Programmed cell Death protein (PD)-1 immunotherapy. Results: Partial PARP-1 inhibition, via gene heterozygosity or a moderate dose of olaparib, protected against colitis-mediated/ APC Min -mediated intestinal tumorigenesis and APC Min -associated cachexia, while extensive inhibition, via gene knockout or a high dose of olaparib, was ineffective or aggravating. A sub-IC50-olaparib dose or PARP-1 heterozygosity was sufficient to block tumorigenesis in a syngeneic colon cancer model by modulating the suppressive function, but not intratumoral migration or differentiation, of MDSCs, with concomitant increases in intratumoral T cell function and cytotoxicity, as assessed by granzyme-B/interferon-γ levels. Adoptive transfer of WT-BM-MDSCs abolished the protective effects of PARP-1 heterozygosity. The mechanism of MDSC modulation involved a reduction in arginase-1/inducible nitric oxide synthase/cyclo-oxygenase-2, but independent of PARP-1 trapping on chromatin. Although a high-concentration olaparib or the high-trapping PARP inhibitor, talazoparib, activated stimulator of interferon gene (STING) in BRCA-proficient cells and induced DNA damage, sub-IC50 concentrations of either drug failed to induce activation of the dsDNA break sensor. STING expression appeared dispensable for MDSC suppressive function and was not strictly required for olaparib-mediated effects. Ironically, STING activation blocked human and mouse MDSC function with no additive effects with olaparib. A metronomic dose of olaparib was highly synergistic with anti-PD-1-based immunotherapy, leading to eradication of MSI high or reduction of MSS tumors in mice. Conclusions: These results support a paradigm-shifting concept that expands the utility of PARP inhibitor and encourage testing metronomic dosing of PARP inhibitor to enhance the efficacy of checkpoint inhibitor-based immunotherapies in cancer.